Between the Place and Non-Place: Architecture and Territory on the Example of Skopje - Sasa Tasic, Mitko Hadzi Pulja, Minas Bakalcev (Cambridge Scholars Publishing, 2015)
It was told that the place is disappearing in the modern contexts. Crisis of modern architecture first started with the crisis of specific places and the essential relation between the architectural object, technology and its place. But has contemporary architecture find the real place, or even became more disconnected to the specific places? Has the contemporary conflict situation uncovered more dramatic relation between the architecture, technology and places? Evident crisis of the places in the modern era is only anticipation of the permanent state of conflict in the contemporary society. Cretan theories already define the relation of historical places and supermodern non-places as well as unique place and its reproduction. But the main aim is how to dial with dynamic status of place in contemporary situations beyond the proposed binary relation of place and non-place and the original and the copy. On the example of the city of Skopje which went through dramatic transformation during the process of modernization is possible to examine some aspect of contemporary places seen through the issue of everyday places. Through selected project we will examine possible approach to places and technologies, which goes beyond the dialectic of place, no-place towards the notion of the territory as principal medium of architectural modification.
Keywords: place, non-place, everyday place, territory